Experimental Study on the Use of Banana and Pineapple Peel Waste as Biofertilizers, tested on Hibiscus Sabdariffa Plant: Promoting Sustainable Agriculture and Environmental Sanitation - Alasa, J. J.; Bashir, A. U.; Mustapha, M.; Mohammed, B. (ARID ZONE JOURNAL OF ENGINEERING, TECHNOLOGY AND ENVIRONMENT, 2021)
Synthetic fertilizers are combination of inorganic substances which causes long-term negative effects on the ecosystem. Indiscriminate agricultural waste disposal especially fruits peels waste when neglected and utilized unproperly can cause environmental pollution and spread of diseases. Fruit peels of banana and pineapple are highly rich in numerous bioactive compounds that can enhance plant growth. This study deals with managing banana and pineapple peel waste as organic fertilizer and compared their effects on the growth of Hibiscus sabdariffa. Three different formulations were prepared from sun dried and finely ground fruits peel of banana and pineapple extract, namely; Sample A containing 100g of banana peels powder, Sample B containing 100g of pineapple peels powder and Sample C containing 100g of a mixture of banana and pineapple peels powder. Four containers were used to collect 2kg of soil each, three of which were treated with the three formulations (Sample A, B and C). The fourth container was labeled sample D (Control). After 30 days of treatment, seeds of Roselle plant were sown in each container and plant growth parameters analyzed periodically. From the results, Sample A showed highest mean number of 3 days to germinate. After 21 days; Sample A had average large leaf area of 14cm2, then Sample B (12.92 cm2), Sample C (10.2 cm2) and Sample D having the smallest (9.6 cm2). After 120 days, average plant height recorded were; Sample A (78cm); Sample B (58), and Sample D (54cm), and sample C showed the lowest average plant height of 47cm. From this study, it was deduced that fruit peel powder formulations can enhance growth and yield of plants, thus limiting the use of chemical fertilizers and protecting the environment. It is recommended that fruits waste should be integrated into farms for enhanced agricultural productivity and clean environment.